Increased Amplitude of the P3a ERP Component as a Neurocognitive Marker for Differentiating Amnestic Subtypes of Mild Cognitive Impairment - Correa-Jaraba, Kenia S.; Lindín, Mónica; Díaz, Fernando (Frontiers in Aging Neuroscience, 2018)
The event-related potential (ERP) technique has been shown to be useful for evaluating changes in brain electrical activity associated with different cognitive processes, particularly in Alzheimer's disease (AD). Longitudinal studies have shown that a high proportion of people with amnestic mild cognitive impairment (aMCI) go on to develop AD. aMCI is divided into two subtypes according to the presence of memory impairment only (single-domain aMCI: sdaMCI) or impairment of memory and other cognitive domains (multi-domain aMCI: mdaMCI). The main aim of this study was to examine the effects of sdaMCI and mdaMCI on the P3a ERP component associated with the involuntary orientation of attention towards unattended infrequent novel auditory stimuli. Participants performed an auditory-visual distraction-attention task, in which they were asked to ignore the auditory stimuli (standard, deviant and novel) and to attend to the visual stimuli (responding to some of them: Go stimuli). P3a was identified in the Novel minus Standard difference waveforms, and reaction times (RTs) and hits (in response to Go stimuli) were also analyzed. Participants were classified into three groups: Control, 20 adults (mean age (M): 65.8 years); sdaMCI, 19 adults (M: 67 years); and mdaMCI, 11 adults (M: 71 years). In all groups, the RTs were significantly longer when Go stimuli were preceded by novel (relative to standard) auditory stimuli, suggesting a distraction effect triggered by novel stimuli; mdaMCI participants made significantly fewer hits than control and sdaMCI participants. P3a comprised two consecutive phases in all groups: early-P3a (e-P3a), which may reflect the orienting response towards the irrelevant stimuli, and late-P3a (l-P3a), which may be a correlate of subsequent evaluation of these stimuli. The e-P3a amplitude was significantly larger in mdaMCI than in sdaMCI participants, and the l-P3a amplitude was significantly larger in mdaMCI than in sdaMCI and Control participants, indicating greater involuntary capture of attention to unattended novel auditory stimuli and allocation of more attentional resources for the subsequent evaluation of these stimuli in mdaMCI participants. The e-P3a and l-P3a components showed moderate to high sensitivity and specificity for distinguishing between groups, suggesting that both may represent optimal neurocognitive markers for differentiating aMCI subtypes.